2020
DOI: 10.3390/insects11120865
|View full text |Cite
|
Sign up to set email alerts
|

Data on Herbivore Performance and Plant Herbivore Damage Identify the Same Plant Traits as the Key Drivers of Plant–Herbivore Interaction

Abstract: Data on plant herbivore damage as well as on herbivore performance have been previously used to identify key plant traits driving plant–herbivore interactions. The extent to which the two approaches lead to similar conclusions remains to be explored. We determined the effect of a free-living leaf-chewing generalist caterpillar, Spodoptera littoralis (Lepidoptera: Noctuidae), on leaf damage of 24 closely related plant species from the Carduoideae subfamily and the effect of these plant species on caterpillar gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Herbivory is one of the most important factors affecting plant fitness [ 58 ], and plant primary photochemistry is the principal plant trait shaping plant–herbivore interaction. The response mechanism of photosystem II photochemistry to insect herbivory and its ability to induce a compensatory mechanism that increases PSII photochemistry in response to herbivore feeding is fundamental in plant resistance to herbivores [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Herbivory is one of the most important factors affecting plant fitness [ 58 ], and plant primary photochemistry is the principal plant trait shaping plant–herbivore interaction. The response mechanism of photosystem II photochemistry to insect herbivory and its ability to induce a compensatory mechanism that increases PSII photochemistry in response to herbivore feeding is fundamental in plant resistance to herbivores [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several plant traits related to growth, defense, and reproduction were measured, as well as the seedling emergence on offspring. Given that the caterpillar performance and growth rate determine the damage they cause on plants [ 63 , 64 , 65 , 66 , 67 , 68 ], we also evaluated the floral herbivore caterpillar development time in the different treatments. We tested whether (i) the plant defense responses to both herbivore group densities would be independent, (ii) the impact on plant fitness of both herbivore group densities would be additive, and (iii) the impact on plant fitness of both herbivore groups would linearly rather than non-linearly increase with their density.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the feeding (or grazing) preferences of the herbivores can determine the relationship between native or invasive autotrophs [ 17 , 18 ]. Recent findings also suggested that mechanisms underlying autotroph palatability could help resolve the inconsistent results of novelty [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that autotrophic characteristics may have the opposite effect on autotroph-herbivore interactions in controlled experimental studies where herbivores are restricted to a single autotroph species than in effects seen in field studies where herbivores are free to move around and cause natural autotroph damage. Future research examining the significance of autotroph features in interactions between autotrophs and herbivores must therefore carefully take into account the context in which the relationships have been observed [ 19 ].…”
Section: Introductionmentioning
confidence: 99%